Population screening in Asia: a unique opportunity to enhance early detection of psychosis? - Woodberry, Kristen A. (Asian J Psychiatr, 2015)
A recent article in this journal (Razali et al., 2015) reports the results of a 2-stage study screening for psychosis risk in Malaysia. The researchers incorporated both selective and indicated prevention strategies and included self-report items probing non-specific “early” experiences as well as attenuated psychotic symptoms associated with the prodromal phase of schizophrenia. Given that increased stigma and reduced services may reduce help-seeking in many Asian countries, population screening may be more important to early detection of individuals at risk for psychosis. Yet, the availability of large population centers and greater trust of providers may make Asian research centers uniquely suited for conducting badly needed research on screening strategies and the role of cultural factors in the emergence of psychosis.